Short-term climate change effects on maize phenological phases in northeast Italy - Berti, Antonio; Maucieri, Carmelo; Bonamano, Alessandra; Borin, Maurizio (Italian Journal of Agronomy, 2019)
This study evaluates the response of maize growing cycle length to meteorological variables at regional scale particularly, in the short-term period, considering global climate change. The experiment was carried out in Veneto Region (Northeast Italy) where maize phenological data collected by the regional network from 2005 to 2007 were combined with temperature data to analyse the relationship between BBCH stages and thermal sum. The effects of climatic changes in the near and medium term on maize phenology and on water requirements were also evaluated over a grid of climatic data obtained from different climatic models. The piecewise analysis gave the best fitting between BBCH and Growing Degree Days observed data characterized by two lines with different slopes with BBCH 70 (beginning of fruit development) as changing stage. The angular coefficient of the first line was 2.6 times than the second one (0.028) suggesting that the early stages of the growing cycle are more sensitive to air temperature. The simulation of maize phenology evolution highlights a modest variation at the 2020-time horizon, while an expected reduction of maize growing cycle of about 10 days has been estimated for 2030-time horizon. Long-term phenological observation are desirable to confirm our findings and to improve the strength of dataset.